EFFECTS OF TRADITIONAL METHOD OF FRYING GARRI ON THE ANTHROPOMETRIC PARAMETERS OF PROCESSORS IN NIGERIA - Adegbite, B. A.; Adeleke, I.; Fasina, O. O.; Ajayi, Francis. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study highlights specific risk postures linked to musculoskeletal disorders in garri frying process. Garri processors selected from six (6) Local Government areas across the 3 Agricultural Zones of Osun state. Two Garri frying workstations were purposively selected based on the availability and popularty being the major Garri workstations, given 12 workstations. Six (6) processors were selected randomly at each workstation given 24 processors from each zone and a total of 72 respondents. Interview and observation methods were adopted for a sound understanding of activities and challenges of garri processors. Descriptive statistic tool was used to analyze data collected. Tape rule, weighing scale, vernier caliper were tools used to measure body height, hand length, thickness, and sit posture. The results shown that 66.7% processors were between age brackets 26 - 45 years. Most processors were primarily female (77.8%) while 22.2% were male, stressing the dominance of female in garri frying venture. Most (88.9%) of the processors had opportunity of attending various levels of educational program while 11.1% benefited from none - formal education system. More so, 43.7% of processors had body weight lower than 50kg while 33.3% and 53% had hand length shorter than 100cm and sit posture lower than 100cm respectively leading to overexertion of body ad this make them susceptible to musculoskeletal pains that threaten health conditions. Over 40% always experienced musculoskeletal pain both at during and after operational tasks. To address inefficiency and health risks, the nature of discomforts must be identified to assist the fabricator of garri fryer or Robotic assistance for maximum performance.